EVALUASI IMPLEMENTASI PROGRAM EXPANDING MATERNAL AND NEONATAL SURVIVAL ( EMAS ) DALAM UPAYA PENURUNAN ANGKA KEMATIAN IBU DAN BAYI DI KABUPATEN BREBES - Sofyan Choirudin; Priyatno Harsasto (Journal of Politic and Government Studies, 2019)
This research was conducted to explain the process of implementing the EMAS program in an effort to reduce maternal mortality rates in Brebes Regency.This study uses a qualitative-descriptive research methodology because this studyexplains phenomena relating to current and experienced situations, attitudes and views that are present at the moment, the relationship between variables contradicts two or more conditions,the effect on a condition, and the difference between facts. This study is conducted by asking for information to the primary subject, namely the source and the main informant and the secondary subject, as a source of additional data in strengthening the data. The data then explains the efforts to implement the EMAS Program in Brebes Regency in order to overcome the highmaternal mortality rate.The results showed that the application of the EMAS program in Brebes District in 2015-2016 had succeeded in reducing maternal mortality. However, overall not optimal because in 2016 when the EMAS Program ended, Brebes still topped the highest maternal mortality rate in Central Java. In addition, it also explains the factors that influence and impact the implementation of the EMAS Program in Brebes Regency in 2015-2016.In the future, the Brebes Regency Government of Brebes Regency needs to pay attention to maternal and child health issues. Determination of regulations supporting the handling of maternal and neonatal emergencies. Repairing facilities and infrastructure in health facilities, so that better services can be created.Keywords: Evaluation, Implementation, EMAS Program, Maternal and Infant Death